Effect of Open Source on Students’ Performance in Electronics and Lecturers’ Readiness for Its Adoption in Institutions in Adamawa State, Nigeria - Ishaku Zechariah; Ajili Tanimu (Darul Yasin Al Sys, 2026)
This study investigated the effect of an open-source instructional approach on students’ academic performance in Digital Electronics and lecturers’ readiness for its adoption in tertiary institutions in Adamawa State, Nigeria. Guided by three research questions and three hypotheses, the study employed a quasi-experimental pre-test–post-test control group design. The study population comprised 48 students and 30 lecturers in Electrical/Electronic Technology, and no sampling was undertaken because the population was manageable. Data were collected using the Digital Electronics Achievement Test (EAT), Electronics Skills Acquisition Test (ESAT), and Lecturers’ Readiness for Adoption of Open Source in Instructional Delivery (LROSAID), all developed by the researcher. The validated EAT and ESAT demonstrated high internal consistency, with Cronbach’s alpha coefficients of 0.92, 0.89, and 0.90, respectively. Data were analyzed using mean and standard deviation to answer the research questions, while ANCOVA and Scheffe’s test were used to test the hypotheses at the 0.05 level of significance. The findings revealed a significant difference in achievement test scores between the open-source instructional strategy and the lecture strategy, as well as a significant difference in skills acquisition in favour of the open-source instructional strategy over the demonstration strategy. However, the results also showed that lecturers were not ready to adopt open source for instructional delivery. The study concludes that the open-source instructional strategy enhanced students’ academic achievement and skills acquisition in Electrical/Electronic Technology, while lecturers’ low readiness for adoption remains a critical implementation challenge. These findings contribute empirical support for the instructional value of open-source approaches and imply the need for institutional efforts to strengthen lecturers’ readiness and encourage the integration of open-source strategies in Electrical/Electronic lesson delivery in Colleges of Education.